2001
DOI: 10.1152/ajpregu.2001.280.1.r255
|View full text |Cite
|
Sign up to set email alerts
|

CYP4A1 antisense oligonucleotide reduces mesenteric vascular reactivity and blood pressure in SHR

Abstract: The cytochrome P-450 4A (CYP4A)-derived arachidonic acid metabolite 20-hydroxyeicosatetraenoic acid (20-HETE) affects renal tubular and vascular functions and has been implicated in the control of arterial pressure. We examined the effect of antisense oligonucleotide (ODN) to CYP4A1, the low K(m) arachidonic acid omega-hydroxylating isoform, on vascular 20-HETE synthesis, vascular reactivity, and blood pressure in the spontaneously hypertensive rat (SHR). Administration of CYP4A1 antisense ODN decreased mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
81
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 27 publications
9
81
0
Order By: Relevance
“…This fall in MAP is consistent with previous findings in the SHR, in which inhibition of the renal formation of 20-HETE with ABT, 13 sodium 10-undecynyl sulfate (10-SUYS), 11 or antisense oligonucleotides 16 have been reported to reduce blood pressure in this strain. ABT has also been reported to lower blood pressure in deoxycorticosterone acetate (DOCA) salt-hypertensive rats 17,18 and in rats with angiotensin II-induced hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This fall in MAP is consistent with previous findings in the SHR, in which inhibition of the renal formation of 20-HETE with ABT, 13 sodium 10-undecynyl sulfate (10-SUYS), 11 or antisense oligonucleotides 16 have been reported to reduce blood pressure in this strain. ABT has also been reported to lower blood pressure in deoxycorticosterone acetate (DOCA) salt-hypertensive rats 17,18 and in rats with angiotensin II-induced hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggested that CYP4A is involved in maintenance of normal blood pressure and contributes to development of hypertension [13,14]. This conclusion has been further supported by Wang and colleagues [15]. In the present study, we further explored the long-term modifications of blood pressure in normotensive and spontaneously hypertensive rats (SHR) by gene delivery of i) rAAV-mediated cytochrome P450 arachidonic acid hydroxylase to overexpress CYP4A1 protein or ii) antisense to block the expression of CYP4A.…”
Section: Construction and Preparation Of Raavmentioning
confidence: 61%
“…CYP4A1 and CYP4A2 antisense oligonucleotides inhibit 20-HETE synthesis in both the vasculature and renal tubules and have an antihypertensive effect in Sprague-Dawley rats and SHRs (47,48). Antisense oligonucleotides have also been used to demonstrate that CYP4A1 plays an important role in mesenteric vascular reactivity (48).…”
Section: Discussionmentioning
confidence: 99%
“…CYP4A1 and CYP4A2 antisense oligonucleotides inhibit 20-HETE synthesis in both the vasculature and renal tubules and have an antihypertensive effect in Sprague-Dawley rats and SHRs (47,48). Antisense oligonucleotides have also been used to demonstrate that CYP4A1 plays an important role in mesenteric vascular reactivity (48). ABT is a mechanism-based inhibitor of renal -and ( -1)-hydroxylation of arachidonic acid and causes a loss of CYP4A apoprotein, a decrease in urinary 20-HETE excretion, and reduction in blood pressure in the SHR and in an ANG II model of hypertension (1,31,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation